What Teachers Never Taught And Writers Feared To Write: Disability in African American Children's Literature - Daniels, Kapria (Disability Studies Quarterly, 2004)
Some African American children's literature reflects the negative stereotypes that are ascribed to individuals with disabilities through the use of implausible, one-dimensional characters that are expected to perform acts of heroism to gain acceptance. The critical use of these and similar texts in educational curriculum is a key step in combating stereotypes about African Americans with disabilities. The impact of established academic institutions on the identity development of African American children with disabilities is discussed.